Pemanfaatan Fitur Layer 7 Protocol Untuk Filter Website Dan Management Bandwidth - Boby Kurniawan; INDONESIA INDONESIA (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
The development of computer networks is one of the tecnologies needed by several companies in carrying out work activites so that they save energy, costs and can access data quickly and precisely. At the class 1 radio frequency spectrum monitoring center in palembang, unprotected internet access and large quotas make user free to access negative or illegal content, sosial media, video streaming and unspecified file downloads. For this reason it is necessary to do alternatives in limiting access to certain sites by limiting access rights in order to anticipate wasting the use of available bandwidth and perform bandwidth management. Based on the existing problems, the research performs website filters dan bandwidth management. The reseacrh was conducted using actin reseacrh methods consisting of diagnosing, action planning, action taking, evaluating dan learning. By using this method, this reseacrh has secceeded in filtering websites and bandwidth management. Based on website filter testing, it can block internet access for negative content, one of which is screenfilm99, while bandwidth management testing limits social media, video streaming dan files download.